The effects of light intensity, fertilization and water depth on the production of Lemna - Sujjat-Al-Azad; Edwards, Peter; Little, David C.; Yakupitiyage, Amararatne; The British Council (Bangkok : Asian Institute of Technology, 1992)
Three experiments were conducted in an outdoor system of fifteen circular concrete tanks each of 2.07m~ area, to investigate the effects of light intensity, urea- N and triple super phosphate- P, and water depth on the production and nutrient uptake of Lemna perpusilla. Experiment 1 involved a fertilization rate of 0.25g N/m3 /day and a water depth of 1.0m at 301., 401., 651., 80/. and 100/. ambient light; Experiment 2 involved a 30/. ambient light in O. lg, 0.2g, 0.3g, 0.4g and 0.5g N/m3 /day (N:P ratio 2:1) in a depth of 1.0m; and Experiment 3 involved a fertilization rate of 0.25g N/m3 /day and with 30/. ambient light, and 0.2m, 0.4m, 0.6m, O.Bm and 1.0m water depths of tanks. The highest extrapolated net yields in the three experiment were, 3.486 tonnes/ha/yr in Experiment 1 with 0.25g N/m3 / day in 1.0m depth and with a 30/. ambient 1 ight when photosynthetic active radiation was 3 to 11 Umol/m-2/s-.1.; and with a fertilization rate of 0.25g N/m3 /d and with 30/.light, in a depth of 0.4m it was 3.515 tonnes/ha/yr, and in Experiment 2 with a varying rates of fertilization and 30/. light, the yield was 3.78 tonnes/ha/yr in the lowest concentration rate of O.lg N/m3 /day . Nitrogen contents in Lemna were not significantly different (p>0.05), but phosphorus contents were significantly different (p<0.05) in the first two experiments. The experiment with depth showed significance differences in nitrogen and phosphorus contents in Lemna (p<0.05). Nitrogen and phosphorus contents increased with nutrient loading rate. Most of the nitrogen added remained in the water in all experiments, except in the experiment with a fertilization rate of O.lg N/m3 /day, with 30/. ambient light; and 0.4m tank in an experiment with 0.25g N/m3/day and 30/. light, where the largest amounts, 55.79/. and 52.8/. respectively, were taken up by Lemna. On the other hand, phosphorus always showed the highest accumulation in the sediments in all experiments, except for the nutrient loading rate and depth mentioned above, where Lemna contained the largest amoL1nt of added nitrogen, 39.12/. and 42.21., respectively.
A thesis submitted to the partial fulfillment of the requirements for the degree of Master of Science, School of Environment, Resources and Development
Thesis (M.sc.) - Asian Institute of Technology, 1992
Keywords: Lemna